E-035 Intra-arterial tissue plasminogen activator (IA-tPA) as first line and salvage therapy to achieve complete reperfusion in acute ischemic stroke. (23rd July 2022) - Waqas, M; Housley, S; Baig, A; Cappuzzo, J; Monteiro, A; Khawar, W; Levy, E; Siddiqui, A
Abstract : Introduction: Despite advances in neurointervention with better mechanical thrombectomy devices and more sophisticated techniques, unsuccessful reperfusion (TICI 0–1) remains the end-result in 1 out of every 10 patients, with most patients who are successfully treated not attaining neurologic independence at 90-days. This is true especially for tough-to-remove clots. We aim to investigate the potential role of intra-arterial tissue plasminogen activator (IA-tPA), as both first-line and salvage therapy after failed completed reperfusion. Methods: A prospectively maintained database was retrospectively searched for acute ischemic stroke patients treated with IA-tPA as either first-line technique or as salvage therapy following failed mechanical thrombectomy (aspiration, stent-retriever, or both) from Jan 2010 to Jan 2022. Patient demographics, comorbidities, presenting NIHSS, IV-tPA, and IA-tPA administration were recorded. Other procedural details such as total no. of passes, first pass effect, and intra- and post-op complications were also recorded. Outcomes were measured in terms of symptomatic intracerebral hemorrhage (sICH), discharge NIHSS, and mRS at 90-days. Results: Forty patients were included in our study (23 female; mean age 68.1 ±13.7 years). Hypertension was the most common comorbidity in 26 cases (65%), followed by hyperlipidemia in 22 (55%). Femoral artery was used as site of access in 36 cases (90%) with radial artery being used in 4 (10%). Median presenting NIHSS was 12 (Range: 5–27) and IV-tPA was administered in 12 cases (30%). IA-tPA was used as first-line therapy for 22 cases (55%), and as salvage therapy in addition to Aspiration in 7 (17.5), with stent-retriever in 3 (7.5%), and with both in 8 cases (20%). First pass effect (mTICI 2B - 3) was achieved in 16 cases (40%), and a final mTICI of 2B-3 attained in 27 total cases (67.5%). In terms of intraoperative complications, clot migration was seen in 2 cases (5%) and dissection in 3 (7.5%). sICH (defined as parenchymal hematoma type II) was seen in 6 cases (15%). Median discharge NIHSS was 4 (Range: 1 - 8) with an mRS of 0–2 at 90-days seen in 23 cases (57.5%). Conclusion: For tough-to-remove clots, IA-tPA as first-line and salvage therapy can be potentially efficacious with adequate results. Disclosures: M. Waqas: None. S. Housley: None. A. Baig: None. J. Cappuzzo: None. A. Monteiro: None. W. Khawar: None. E. Levy: 2; C; Claret Medical, GLG Consulting, Guidepoint Global, Imperial Care, Medtronic, Rebound, StimMed, Misionix, Mosiac, Clarion, IRRAS. 3; C; Medtronic. 4; C; NeXtGen Biologics, RAPID Medical, Claret Medical, Cognition Medical, Imperative Care, Rebound Therapeutics, StimMed, Three Rivers Medical. 6; C; Reimbursement for travel and food for some meetings with the CNS and ABNS. A. Siddiqui: 2; C; Amnis Therapeutics, Apellis Pharmaceuticals, Inc., Boston Scientific, Canon Medical Systems USA, Inc., Cardinal Health 200, LLC, Cerebrotech Medical Systems, Inc., Cerenovus, Cerevatech Medical, Inc., . 4; C; Adona Medical, Inc., Amnis Therapeutics, Bend IT Technologies, Ltd., BlinkTBI, Inc, Buffalo Technology Partners, Inc., Cardinal Consultants, LLC, Cerebrotech Medical Systems, Inc, Cerevatech Medical.